A nonlinear framework for stiction compensation in ratio control loop. (August 2020) - Mishra, Puneet; Kumar, Vineet; Rana, K.P.S.
Abstract: Stiction nonlinearity in control valves has always attracted attention of researchers as it induces limit cycles. In ratio control loops, the problem is further enhanced owing to the presence of significant measurement noise and frequent variations in setpoint of inner flow control loop, usually present in these loops. In this paper, to suppress these unwanted oscillations, a nonlinear control-cum-compensation framework, nonlinear proportional integral controller (NPIC), has been investigated. Based on comparative experimental performance investigations, with other recent state-of-art and conventional schemes, it was observed that NPIC controller outperformed other controllers, in ratio control loop employing sticky pneumatic control valve. Highlights: Nonlinear PI controller (NPIC) is explored for stiction compensation. Experimental studies for ratio control are performed with sticky pneumatic control valves. Detailed tuning methodology for NPIC and stiction combating intelligent controller. Comprehensive comparative analysis with inline state-of-art compensation method. NPIC provided more robust and effective stiction compensation.